PERANCANGAN BUKU CERITA BERGAMBAR DIET PLASTIK UNTUK MENJAGA KELESTARIAN LINGKUNGAN - Evita Yolanda Sari; syafwandi syafwandi (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
This design is motivated by the large amount of plastic waste caused by the increasingly severe impact of plastic waste on the environment. Various efforts have been made to reduce plastic waste, but public awareness is still low. This final project aims to design an educational media for children aged 9-11 years in the form of pictorial stories. The approach used is to make this pictorial story, among others; illustration approach, pictorial story approach, and environmental awareness approach. The design method used is the Four-D method (Define, Design, Develop, Disseminate). The main media chosen was picture story books. For promotional needs, the supporting media chosen are: T-shirts, T-shirts, bookmarks, X-Banners, E-Books, posters, and Tumblr.Keywords: Picture Story Book, Plastic Diet, illustration, Environment